2006
DOI: 10.1002/cncr.21971
|View full text |Cite
|
Sign up to set email alerts
|

The risk of secondary malignancies over 30 years after the treatment of non‐Hodgkin lymphoma

Abstract: BACKGROUND Survivors of non‐Hodgkin lymphoma (NHL) are at increased risk for developing secondary malignancies. For the current study, the authors quantitated this risk in a group of NHL survivors over 30 years of follow‐up. METHODS Standardized incidence ratios (observed‐to‐expected [O/E] ratio) and absolute excess risk of secondary malignancies were assessed in 77,876 patients who were diagnosed with NHL between 1973 and 2001 from centers that participated in the National Cancer Institute's Surveillance, Epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
124
2
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 171 publications
(147 citation statements)
references
References 29 publications
17
124
2
4
Order By: Relevance
“…By using this number, any subsequent diagnosis of mesothelioma among patients with HL or NHL was identified, including any malignancies after a second malignancy. Similar to the study by Tward et al 19 patients with <2 months of follow-up were excluded, including those who had 2 malignancies diagnosed within a 2-month period. The month and year of diagnosis were extracted along with age at diagnosis, vital status, radiation treatment, surgical treatment, and duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By using this number, any subsequent diagnosis of mesothelioma among patients with HL or NHL was identified, including any malignancies after a second malignancy. Similar to the study by Tward et al 19 patients with <2 months of follow-up were excluded, including those who had 2 malignancies diagnosed within a 2-month period. The month and year of diagnosis were extracted along with age at diagnosis, vital status, radiation treatment, surgical treatment, and duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] It is only very recently, however, that epidemiology studies have shown associations between mesothelioma and radiation treatment for NHL and testicular cancer. 7,19 Travis et al 7 used SEER data through 2001, enhanced by data from other population-based registries in Canada and Europe, to identify 40,576 survivors of testicular cancer who were followed for second cancers. A statistically significant increased risk of pleural mesothelioma was reported among men who received supradiaphragmatic radiation (relative risk [RR], 4.0: 95%CI, 2.0-8.1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations